PENGARUH PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION DAN DISKUSI TERHADAP HASIL BELAJAR IPA KELAS IV SD - Lalu Warige Hadinata; Sugeng Utaya; Punaji Setyosari (Graduate School of Universitas Negeri Malang, 2017)
The research aims to determine the effect of STAD and discussion on learning outcomes of classroom learning for science at 4th grade. The design of this research used a quasi-experimental design with nonequivalent control group design. Research was conducted in the 4th grade students of SDN 2 Kekeri West Lombok It’s consist of 19 students in 4th grade/a as an STAD and 19 students at 4th grade/b as the discussion. Analysis of learning outcomes data using the Independent Sample T Test with IBM SPSS 24. The analysis showed: (1) there were no significant differences in learning outcomes among students that learned STAD and students that learned discussion. (2) STAD and discussion has an effect on student learning outcomes of 4th grade.Penelitian bertujuan untuk mengetahui perbedaan hasil belajar STAD dan diskusi pelajaran IPA kelas IV. Rancangan penelitian ini menggunakan eksperimen semu dengan bentuk nonequivalent control group design. Penelitian dilaksanakan pada siswa kelas IV SDN 2 Kekeri Lombok Barat terdiri dari 19 siswa kelas IV/a dengan STAD dan 19 siswa kelas IV/b dengan diskusi. Analisis data hasil belajar menggunakan Independent Sample T Test dengan IBM SPSS 24. Hasil analisis menunjukkan (1) tidak ada perbedaan hasil belajar yang signifikan antara siswa yang dibelajarkan STAD dan siswa yang dibelajarkan diskusi. (2) STAD dan diskusi mampu meningkatkan hasil belajar siswa pada kelas IV.